Jnana Marga Yoga Dan Jengah Fusi Local Narrative Eskatologi Agama Hindu Dan Kebudayaan Masyarakat Bali Sebagai Indigenisasi Dalam Mengonstruksi Resiliensi Akademik Di Abad 21 - Ketut Agus Nova (Purwadita : Jurnal Agama dan Budaya, 2022)
The purpose of this study is to explain that there is a linearity between the conceptions of Jnana Marga Yoga and jengah as a local narrative in an effort to build a learning mentality as well as the resilience capability of learners to face the reality and dynamics of the 21st century. This study found the fact that verstehen paradigm in collaboration with Hindu religious propositions (Jnana Marga Yoga) + local cultural values (jengah) + pasraman existence = academic resilience (learning ethos, not quickly satisfied, not quick to give up, has a desire to grow) which is applied in the world of education. The presence of Jnana Marga Yoga and Jengah as a compendium will be more organized by institutionalizing these teachings in local educational institutions with Hindu religious based, known as Pasraman. With the presence of Pasraman, the teachings of science and resilience skills will be well organized and systematized, as an effort to deal with the reality, fluctuations and dynamics of the 21st century. Keywords: Jnana Marga Yoga, jengah, pasraman